Educational curriculum materials and pedagogical practice: what is(are) the message(s)? - Reinaldo Feio de Lima; Andréia Maria Pereira de Oliveira (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The objective of this article is to identify and understand the message of pedagogical practice represented in Educational Curriculum Materials' texts. We adopted document analysis as a procedure and used the concepts of classification and framing developed by Basil Bernstein. The results point to at least two messages: of the material, characterized by the transparency and structure of the text, and of the pedagogical practice portrayed and characterized by the sequencing of actions and interactions of the teacher on "how" to familiarize and overcome students' difficulties during the implementation of the math task. Therefore, the messages present in MCE' texts converge to guidelines aimed at practice with methodological guidelines indicating aspects to be considered, and mathematical content previously produced with the participation of teachers for pedagogical practice.